Peran Badan Usaha Milik Desa Urip Jaya dalam Upaya Peningkatan Ekonomi Masyarakat - Kustin Hartini (IPM2KPE, 2023)
This research aims to explore the role of BUMDes Urip Jaya in efforts to improve the economy of the people of Sumber Urip Village, Rejang Lebong Regency, Bengkulu Province. This research method is qualitative research with a descriptive approach. The results of the research show that the role of BUMDes Urip Jaya in efforts to improve the economy of the Sumber Urip village community has generally been going well, this can be seen from the ongoing activities of BUMDes business units including the Payment Point Online Bank (PPOB) business unit as a payment access center. electricity and water, a bokashi unit as a fertilizer supply service center and a tourism unit as a center for managing tourism village potential and also a tent unit which provides various kinds of tents for community celebration events. Conclusion. Keywords: BUMDes, Community Economy, Role of BUMDes